Cultural Meaning and the Experience of Hormone Drug Use Among Transgender Women Undergraduate Students in Southern Thailand - Sottiyotin, Tida; Apinuntachart, Pacharapol; Amornlak, Yanisa; Muenlamai, Tidarat; Adulyarat, Najmee (Journal of Population and Social Studies [JPSS], 2024)
The practice of feminizing hormone drug use among transgender women is established but not well understood. This study used an interpretive phenomenological approach to explore the significance and experiences of hormone drug use among transgender women (TGW) undergraduate students. The study involved twenty-one participants in semi-structured interviews and applied thematic analysis to the data. Findings reveal that participants view hormone drug use as crucial for personal satisfaction and social acceptance. Their use of these drugs varied, including changes in medication type, dosage adjustments, and intermittent or consistent use, tailored over time to individual needs. These variations were influenced by factors encouraging or discouraging hormone drug use and by perceptions of recent hormone drug use, whether positive or negative. The study highlights the essential role of hormone drug use in transgender individuals' lives, emphasizing the need for greater attention and support in social and healthcare systems. It points to the importance of responsible use of feminizing hormones, addressing the unique needs of transgender women, and promoting a health and well-being supportive environment.